Carbon Flux Analysis Of Lipid Biosynthesis Pathways In Oil Palm (Elaeis Guineensis Jacq. Tenera) - Emily, Quek Ming Poh (2002)
The aim of this study was to investigate the carbon flux through lipid biosynthesis pathways in the oil palm (Elaeis guineensis Jacq. tenera) using metabolic control analysis (MCA). Three types of tissue from oil palm, namely liquid culture, plastid and mesocarp were used. The results showed mesocarp tissue was the most suitable tissue for carbon flux analysis because it incorporated the radioactive precursors mainly into triacylglycerol (TAG). Further analysis on different stages of fruit development was carried out using mesocarp tissue at 12, 1 5 and 20 weeks after anthesis (JV AA). It was confirmed that 2 0-W AA mesocarp tissue was the best stage of fruit development for metabolic flux studies because it reflected biosynthesis of storage lipid. Three modes of radiolabel introduction into the oil palm fruits were investigated, namely injecting the radiolabel into the fruits still attached to the palm, injecting the radiolabel into the loose fruit and injecting the radio label into incubation mixture containing meso carp tissue slices. The level of radioactivity in fruits attached to the palm was lower than the other two modes of radiolabel introduction. Carbon flux of lipid b iosynthesis pathways was modulated by temperature and the inhibitor 2-bromooctanoate. Radiolabels [ 1_14C]